CRITICAL DISCOURSE ANALYSIS OF HATE SPEECH ON INSTAGRAM: A POLITICIAN’S EDUCATIONAL DOCUMENTS IN INDONESIA, 2025 - Opirman Waruwu (Universitas Nias Raya, 2025)
Hate speech has become an increasingly prevalent issue on social media platforms. Instagram, initially designed as a social networking space, has evolved into a medium for public and political discourse while simultaneously facilitating the spread of hate speech. This study examines the forms and linguistic strategies of hate speech found in Instagram comments related to the controversy surrounding an Indonesian political figure’s educational credentials. Using a qualitative method and a Critical Discourse Analysis (CDA) approach, data were collected through documentation and purposive sampling. A structured recording technique was applied to document, categorize, and code relevant comments. The results found show that hate speech appears in the form of insults, defamation, unpleasant acts, and the spread of potentially misleading or false information. Such expressions are not only emotional but also display structured patterns intended to construct stigma and delegitimization. These findings emphasize the importance of strengthening digital literacy and implementing regulations to foster more ethical and responsible online interaction.